(untitled) (The Pakistan Development Review, 2008)
Foreign aid has played a significant role in Pakistan’s economic development. In the 1950s and 1960s it was aid that helped propel the high rates of growth of the economy. Again in the 1980s and the early 21st century, aid has supported the high levels of growth in the economy. Many books and articles have looked at the role of aid in a narrow economic perspective, but the present volume looks at aid in a political economy framework. The time-period covered is 1960-2002, and both bilateral as well as multilateral aid flows are included in the analysis. Seven chapters makeup the book, along with a number of tables at the end which throw light on the author’s analysis. The theoretical framework followed is one that examines both the donor’s and the recipient’s need for aid. The objectives and the needs of both do not always match. Chapters 3, 5, and 6 form the crux of the book. Chapter 3 discusses and examines the politico-economic factors that are responsible for the allocation of aid........